Social Capital as Main Pillar for Tourism Industry - Made Handijaya Dewa; Dewa Gede Sidan Raeskyesa; Alavi Ali; I Dewa Made Agung Kerta Nugraha (Soshum: Jurnal Sosial dan Humaniora, 2020)
This paper has an objective to analyze the role of socio-culture in the tourism sector by posing a central question: how does social capital attract tourists in Bali province? The study uses qualitative approach by collecting data through observation on human behavior and social capital phenomenon, and through systematic in-depth interview. Based on the research, social capital dimension that have been formulated are Personal Relationship, Social Network Support, Civic Engagement, and Trust and Cooperative Norms. The social capital dimensions play significant roles as the four elements have attractively, or attached for tourist to come and to stay permanently in Bali. It has been confirmed by the local societies and authorities, and how the local activities to maintain their traditions. Value degradation of social capital values have been shown, on the other side, in several touristic areas, along with massive investments and tourism development.